1976
DOI: 10.2113/gsecongeo.71.1.157
|View full text |Cite
|
Sign up to set email alerts
|

Detrital gold, uranium, and pyrite concentrations related to sedimentology in the Precambrian Vaal Reef placer, Witwatersrand, South Africa

Abstract: The Vaal Reef placer was deposited during the Vaal Stage of the Upper Witwatersrand System, approximately 2,500 million years ago. The stratiform deposit is up to 5 feet thick and covers an area of over 100 square miles. It was discovered in 1934 and today is exploited at eight adjacent gold mines which produce approximately 16 percent of South Africa's total gold output.This study integrates stratigraphical, structural, petrological, and mineralogical data with a comprehensive set of sedimentological data to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 2 publications
0
57
0
Order By: Relevance
“…The occurrence of mud pebbles in high-energy sedimentary environments is known (TIETZE, 1975;KARCZ, 1969), andMINTER (1976) According to RAMDOHR (1957RAMDOHR ( , 1975, brannerite is either a pegmatitic mineral or a secondary mineral formed by the "pronto-reaction" from uraninite and ruffle under elevated temperatures. According to FERRIS & RUOD (1971), brannerite in the Blind River district, Canada, "was formed from the decomposition of ihnenite to futile and anatase in the presence of dissolved uranium during diagenesis".…”
Section: Manganesementioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of mud pebbles in high-energy sedimentary environments is known (TIETZE, 1975;KARCZ, 1969), andMINTER (1976) According to RAMDOHR (1957RAMDOHR ( , 1975, brannerite is either a pegmatitic mineral or a secondary mineral formed by the "pronto-reaction" from uraninite and ruffle under elevated temperatures. According to FERRIS & RUOD (1971), brannerite in the Blind River district, Canada, "was formed from the decomposition of ihnenite to futile and anatase in the presence of dissolved uranium during diagenesis".…”
Section: Manganesementioning
confidence: 99%
“…2). PaETORIUS (1975) and MINTEr~ (1976) have shown that sedimentological ore control was the factor governing the distribution and concentration of gold and detrital minerals and that some ore minerals can be attributed to a later recrystal- (1974,1975).…”
Section: Introductionmentioning
confidence: 99%
“…This is obviously not the case; genesis of placer deposits is rather complex and still partially understood due to the interfingering of sedimentological, geomorphological, tectonic and mineralogical processes responsible for the accumulation of these heavy minerals. A wealth of publications exists on these ore deposits and only a few can be cited here (Minter, 1976;Komar and Wang, 1984;El Gemmizi, 1985;Hattori et al, 1992;Cabri et al, 1996;Hamilton and Collins, 1998;Roy, 1999;Dill 2001). Many papers have been published on placers in glacial-fluvial depositional environments mainly containing gold (Levson and Morison, 1996;Duk-Rodkin, 1997) and on diamond accumulations in tropical and arid environments (Thomas et al, 1985;Johnson and McQueen, 2001;Teeuw, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these criteria, the oldest recognized evidence of aeolian deposition is from the 3.2 Ga Moodies Group of South Africa (Simpson et al, 2012). Other notable Archaean examples of wind processes are ventifacts associated with placer deposits in the 2.9 Ga Witwatersrand Supergroup, South Africa (Minter, 1976; and sand-sheet deposits composed of aeolian stratification from the 2.6 Ga Minas…”
Section: Aeolian Sedimentation and Secular Changementioning
confidence: 99%